Extracurricular Special Service Management in Improving Students' Soft Skills (Multiple Case Studies at SMA Negeri 2 Malang and SMK Negeri 1 Purwosari) - Kusumawardhani, Dyah; Burhanuddin, Burhanuddin; Sunarni, Sunarni (Universitas Negeri Malang, 2024)
The purpose of this research is to describe in detail the management of extracurricular special services in improving students’ soft skills at SMA Negeri 2 Malang and SMK Negeri 1 Purwosari, starting from the management process, strategy, supporting factors, and inhibiting factors and their solutions. This research uses a qualitative approach with a multiple case studies design to obtain more in-depth and varied data. The results of this study explain about improving students’ soft skills through extracurricular management processes, extracurricular strategies, extracurricular supporting factors, and extracurricular inhibiting factors and their solutions at SMA Negeri 2 Malang and SMK Negeri 1 Purwosari. Keywords: special service management; extracurricular activities; soft skills